Status of Health, Education and Income Inequality in Iran - Hamed Seddighi; Mir-Taher Mousavi (Shahid Sadoughi University of Medical Sciences, 2019)
Abstract In the age of globalization, development and progress are a multidimensional and complex problem that is not measured by economic measures alone, and various issues related to people's welfare, governance, attention to the planet and the environment, the participation of various groups also considered. In this study, we tried to investigate this issue in several aspects of Iran's global situation. This study was descriptive and data collection was done by documentary study method. In this study, we have tried to study various global databases, studies and global reports, the status of Iran in the fields of environment, children education, health, economic inequality and gender divide. Studies have shown that inequality in income and wealth, although the situation in Iran is better than the Persian Gulf countries but more inequality than other parts of the world, including the United States and Western Europe. In terms of health, among the fifty major causes of death, Iran is ranked first and fourth in global terms due to road accidents and illicit drug use. At the same time, mortality from liver cancer, skin cancer, epilepsy, cervical cancer, kidney cancer and cancer are in a good condition compared to other countries in the world. In the field of education, the state of Iran in primary education, the exclusion of children from primary education, the guarantee of equal access for women and men to higher education and the eradication of gender inequality in participating in education is a good situation than in other parts of the world, but in The number of preschool years and pre-school education has been weaker than many other countries. In the field of environmental protection in Iran, it has a bad record. Based on various indicators such as air quality, water, health, heavy metals, biodiversity, forest protection, fisheries, climate and energy, air pollutants, water resources, Iran has poor ranking in the world. In the context of the gender gap, Iran has ranked poorly in 140 out of 144 countries with indicators of opportunity and economic participation, education, health and life and political rehabilitation